Comparison of traditional instruction versus nontraditional learning to improve trainee knowledge of urine culture practices in catheterized patients - Catherine A. Gao; Rupak Datta; Dana Dunne; Louise-Marie Dembry; Richard A. Martinello; Manisha Juthani-Mehta; Sonali D. Advani (Cambridge University Press, 2022)
We surveyed trainees about their urine culture practices and assessed the impact of an educational intervention delivered electronically and in person. Trainee scores improved across all levels of training and across all questions on the postintervention survey, but there was no difference in scores by mode of education (P = .91).